The Work Situation of the Academic Profession in Europe: Findings of a Survey in Twelve Countries
XIV, 290 p.
Keywords: This book presents the analysis of the representative survey about the academic profession in twelve European countries. Higher education in Europe has experienced a substantial change in recent years: Expansion progresses further, the expectation to deliver useful contributions of knowledge to the “knowledge society” is on the rise, and efforts to steer academic work through external forces and strong international management are more widespread than ever. Representative surveys of the academic profession in twelve European countries show how professors and junior staff at universities and other institutions of higher education view the role of higher education in society and their professional situation and how they actually shape their professional tasks. Academics differ across Europe substantially in their employment and working conditions, their views and their activities. Most of them favour the preservation of a close link between teaching and research and feel responsible for both theory and practice. Most consider efforts to enhance academic quality and social relevance as compatible. The overall satisfaction with their professional situation is rather high.